Air dehumidification by cooled adsorption in silica gel grains. Part I: Experimental development of a prototype. (25th August 2016) - Pistocchini, Lorenzo; Garone, Silvia; Motta, Mario
Highlights: Development and testing of a fixed bed adsorption dehumidifier. Adsorption beds made by finned tube heat exchangers packed by silica-gel grains. Cooled adsorption allows reducing the regeneration temperature below 55 °C. Optimized geometry of packed beds entails low pressure losses in the air side. Low cost dehumidifier provides promising thermal and electric performances. Abstract: This work deals with the development and testing of a fixed-bed adsorption dehumidifier, designed to manage the latent load in air conditioning. The system is based on the batch operation of two finned tube heat exchangers, where silica gel grains are packed between the fins. The water flow in the tubes provides the required heat supply and rejection, allowing a quasi-isothermal operation. As a result, the heat supply temperature can be reduced below 55 °C, fostering the use of waste heat and solar thermal collectors. Moreover, the inversion of the air flow direction between the operating stages is not needed to achieve suitable levels of dehumidification, enabling a design simplification. The test campaign has shown that the electric and thermal performances of the low-cost prototype highly depend on the operating conditions, but both reach very promising values under the worst environmental conditions, when the energy consumption is higher.